Physical Activity Levels and Exercise Perceptions in Overweight and Obese Women - Margaret Varghese; Anahita R Shenoy Basti; Chandralekha N (National Board of Examinations Journal of Medical Sciences)
Objectives: Physical activity (PA) is a crucial component of a healthy lifestyle, with numerous benefits for overall well-being and the prevention of non-communicable diseases (NCDs). Physical activity by its ability to boost our immune system can also reduce the burden of communicable disease. Although there is considerable knowledge and research about barriers to activity, the level of physical inactivity and obesity is on a steep rise. Indicating that the interventions in place do not effectively target the barriers and a failing exists to recognize other factors influencing inactivity. The objective of this study is to investigate the levels of physical activity and the perceived benefits and barriers to exercise among overweight and obese women. Methods: This descriptive observational cross-sectional study involved 96 women aged 18-64 years. They underwent clinical examinations, BMI and body fat parameters were assessed. Global Physical Activity Questionnaire (GPAQ) and Exercise Benefits and Barrier scale were administered. GPAQ evaluates physical activity across various domains, while EBBS gauges individuals' perceptions of exercise benefits and barriers. Results: We found that 34.3% of the participants were physically inactive, 27.08% were moderately active, and 38.5% were highly active based on their MET scoring on the GPAQ questionnaire. Time spent on household chores and workplace attributed to most of the physical activity performed. The subjects were aware of the benefits of exercise. Time restraint, and viewing exercise as tiresome or hard work rather than a form of entertainment were some of the barriers. Conclusion: The physical inactivity among overweight and obese women was found to be 34.3%. Lack of time and personal fatigue was cited as being one of the major limiting factors to performing exercise. Interventions targeting these barriers as well as strategies that target the way exercise is perceived by the population, need to be initiated to enhance the levels of physical activity.